Performance and future directions of transition metal sulfide‐based electrode materials towards supercapacitor/supercapattery. Issue 1 (1st July 2021) - Das, Arya; Raj, Benjamin; Mohapatra, Mamata; Andersen, Shuang Ma; Basu, Suddhasatwa
Abstract: Advanced and sustainable energy storage technologies with tailorable electrochemically active materials platform are the present research dominancy toward an urgent global need for electrical vehicles and portable electronics. Moreover, intensive efforts are given to screen the widely available low‐cost materials with a focus to achieve superior electrochemical performance for the fabrication of energy storage devices. Transition metal‐based sulfides have prodigious technological credibility due to their compositional‐ and morphological‐based tunable electrochemical properties. Here the significant advances and present state‐of‐the‐art of such assured materials in different energy storage devices are discussed. Assessment of the intensive work invested in the progress of transition metals such as V, Mn, Fe, Co, Ni, Cu, Zn Mo, and W based sulfides along with their structural/compositional engineering and addressable aspects for electrochemical performance enhancement are highlighted. Additionally, discussions on critical strategies for decisive mechanistic and kinetic views for charge storage phenomena with key challenges, such as volume expansions, low stability, and sluggish kinetics, are discussed. Finally, the challenges and future prospects demands for strategic approaches of such materials with prominence in futuristic directions are concluded. This article is categorized under: Energy Efficiency > Science and Materials Energy Research & Innovation > Science and Materials Abstract : Metal sulfides as efficient electrode materials for supercapacitors.